l-Tetrahydropalmatine, an Active Component of Corydalis yanhusuo W.T. Wang, Protects against Myocardial Ischaemia-Reperfusion Injury in Rats - Han, Yi; Zhang, Wen; Tang, Yan; Bai, Wenli; Yang, Fan; Xie, Liping; Li, Xiaozhen; Zhou, Suming; Pan, Shiyang; Chen, Qi; Ferro, Albert; Ji, Yong (PLOS ONE, 2012)
l-Tetrahydropalmatine (l-THP) is an active ingredients of Corydalis yanhusuo W.T. Wang, which protects against acute global cerebral ischaemia-reperfusion injury. In this study, we show that l-THP is cardioprotective in myocardial ischaemia-reperfusion injury and examined the mechanism. Rats were treated with l-THP (0, 10, 20, 40 mg/kg b.w.) for 20 min before occlusion of the left anterior descending coronary artery and subjected to myocardial ischaemia-reperfusion (30 min/6 h). Compared with vehicle-treated animals, the infarct area/risk area (IA/RA) of l-THP (20, 40 mg/kg b.w.) treated rats was reduced, whilst l-THP (10 mg/kg b.w.) had no significant effect. Cardiac function was improved in l-THP-treated rats whilst plasma creatine kinase activity declined. Following treatment with l-THP (20 mg/kg b.w.), subunit of phosphatidylinositol 3-kinase p85, serine473 phosphorylation of Akt and serine1177 phosphorylation of endothelial NO synthase (eNOS) increased in myocardium, whilst expression of inducible NO synthase (iNOS) decreased. However, the expression of HIF-1α and VEGF were increased in I30 minR6 h, but decreased to normal level in I30 minR24 h, while treatment with l-THP (20 mg/kg b.w.) enhanced the levels of these two genes in I30 minR24 h. Production of NO in myocardium and plasma, activity of myeloperoxidase (MPO) in plasma and the expression of tumour necrosis factor-α (TNF-α) in myocardium were decreased by l-THP. TUNEL assay revealed that l-THP (20 mg/kg b.w.) reduced apoptosis in myocardium. Thus, we show that l-THP activates the PI3K/Akt/eNOS/NO pathway and increases expression of HIF-1α and VEGF, whilst depressing iNOS-derived NO production in myocardium. This effect may decrease the accumulation of inflammatory factors, including TNF-α and MPO, and lessen the extent of apoptosis, therefore contributing to the cardioprotective effects of l-THP in myocardial ischaemia-reperfusion injury.